Odpowiedzi

2010-01-07T21:55:29+01:00
X-3/5 -y+1/2=1-x+y
4x-1/3-y-3/6=-2x+2y

x-y+x-y=3/5-1/2
4x-y-2y+2x=1/3+3/6

2x-2y=6/10-5/10
6x-3y=5/6

2x=6/10-5/10+2y
3(6/10-5/10+2y)-3y=5/6

2x=6/10-5/10+2y
18/10-15/10+6y-3y=5/6

2x=6/10-5/10+2y
3y=54/30-45/30+25/30

2x=6/10-5/10+2y
3y=34/30

2x=6/10-5/10+2y
y=34/90

2x=6/10-5/10+68/90
y=34/90

2x=54/90-45/90+68/90
y=34/90

2x=77/90
y=34/90

x=144/90
y=34/90
Najlepsza Odpowiedź!
  • Roma
  • Community Manager
2010-01-07T22:15:50+01:00
( x-3/5 - y+1/2 = 1-(x-y) /*10
(4x-1/3 - y-3/6 = -2(x-y) /*6

( 2(x - 3) - 5(y+1) = 10 - 10(x-y)
( 2(4x - 1) - (y - 3) = -12(x - y)

( 2x - 6 - 5y - 5 = 10 - 10x + 10y
( 8x - 2 - y + 3 = -12x + 12y

( 2x - 5y + 10x -10 y = 10 + 6 + 5
( 8x - y +12x - 12y = 2 - 3

( 12x - 15y = 21 /:3
( 20x - 13y = -1

( 4x - 5y = 7 /*(-5)
( 20x - 13y = -1

( -20x + 25y = -35
( 20x - 13y = -1
_______________
25y - 13y = -35 - 1
12y = - 36 /:12
y = - 3

4x - 5y = 7
4x - 5*(-3) = 7
4x + 15 = 7
4x = 7 - 15
4x = -8 /:4
x = -2

( x = -2
( y = -3







2 3 2